2018
DOI: 10.1371/journal.pone.0200060
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of AAV-delivered single-chain variable fragments for the treatment of methamphetamine abuse

Abstract: Methamphetamine (METH) substance abuse disorders have major impact on society, yet no medications have proven successful at preventing METH relapse or cravings. Anti-METH monoclonal antibodies can reduce METH brain concentrations; however, this therapy has limitations, including the need for repeated dosing throughout the course of addiction recovery. An adeno-associated viral (AAV)-delivered DNA sequence for a single-chain variable fragment could offer long-term, continuous expression of anti-METH antibody fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…In both this study (data not shown) and as previously reported with the same concentration of AAV, no lasting adverse effects were observed as a result of the high AAV dose (Hay et al, 2018).…”
Section: Physiological Efficacysupporting
confidence: 86%
See 4 more Smart Citations
“…In both this study (data not shown) and as previously reported with the same concentration of AAV, no lasting adverse effects were observed as a result of the high AAV dose (Hay et al, 2018).…”
Section: Physiological Efficacysupporting
confidence: 86%
“…One pharmacological approach is to use anti-METH monoclonal antibodies (mAbs) as pharmacokinetic antagonists to block or blunt METH effects. Unlike a small molecule medication, which would selectively block multiple receptors for extended periods of time, mAbs sequester METH in the circulatory system Stevens, Tawney, et al, 2014;Hay et al, 2018) and reduce METH entry into critical tissues like the central nervous system (CNS) and the cardiovascular system. Pharmacokinetic assays demonstrated that an anti-METH mAb therapy, administered as a bolus i.v.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations